Pandangan Hamka terhadap Pengkajian Ulum Al-Quran dalam Tafsir Al-Azhar - Zulfikri; Kirin, Arwansyah (Advances in Humanities and Contemporary Studies, 2020)
The study of Ulum al-Quran is very important for the development of Tafseer studies. This science continues to develop from classical times to the present. The theories of Ulum al-Quran is essential to be studied, understood, and used by commentators to find the meaning, purpose, and broad understanding of the verses of the Quran. One of the works that have not escaped the theory of Ulum al-Quran is Tafsir al-Azhar by Hamka. This tafsir is widely found and read in the archipelago, especially in Indonesia. In interpreting the Quran, Hamka explained his thoughts on the Ulum al-Quran, which supported his interpretation. Therefore, it is essential to explain his views so that the public, especially Quranic scholars, can know them. The purpose of this study is to analyze Hamka’s views on the study of Ulum al-Quran in Tafsir al-Azhar and reveal the extent of his knowledge and status as an interpreter through his book Tafsir al-Azhar. The method for this study is qualitative, through the use of library research and analysis design of the content in the book of Tafsir al-Azhar. This research was conducted with a descriptive-analytical method and focused on the literature review. As a result, in reviewing the definitions of Ulum al-Quran Hamka, he only explains simply. He sometimes gives several theoretical examples of the meaning of the Quran, Tafsir, Ta’wil, I’jaz, Muhkam-Mutasyabih, Makiyah-Madaniyah, Nasikh-Mansukh, Asbab al-Nuzul. Here the author completes and strengthens the understanding from interpreting the verses related to the Ulum al-Quran. Then Hamka more on strengthening the understanding of Ulum al-Quran from Salaf and Khalaf scholars. So that readers of the tafsir can understand more clearly the interpretation of the verses of the Qur’an correctly and efficiently. Then, Hamka has adequate capacity and knowledge in the science of Interpretation. Moreover, it can explain to the public about the study of the ’Ulum al-Quran in a simple manner.